Interpellating Hyphenated Medusas: Pearl Cleage's Chain and Rhodessa Jones' Big Butt Girls, Hard Headed Women (International Journal Online of Humanities, 2020)
Here they are, returning, arriving over and again, because the unconscious is impregnable. They have wandered around in circles, confined to the narrow room in which they've been given a deadly brainwashing. You can incarcerate them, slow them down, get away with the old Apartheid routine, but for a time only. As so as they begin to speak, at the same time as they're taught their name, they can be caught that their territory is black. Hélène Cixous, "The Laugh of the Medusa"1975, p. 877Monomaniac phallic acculturation aligns femininity with whatever attributes repudiated by the masculine world. A male is deemed to be the locus of power and restraint within the family, as well as, its representative in the outer world. In contradiction, a female is commonly associated with passivity, masochism and narcissism. This phallogocentric notion is originated in a misogynic patriarchal ideology that gives rise to the leitmotif of female otherness. The perception of gender boundaries is necessary for males who promote their logic of dualism through incarcerating females into only two fixed metaphors: Angel or Mad. Pearl Cleage1 and Rhodessa Jones2 in their plays Chain (1991) and Big Butt Girls, Hard-Headed Women (1990), respectively, press against the externally and internally imposed boundaries confining the African American feminine expression. Theirs is a concurrent issue which gives a collective redefinition of sisterhood; they do not only seek helping black females, but also any female to transcend the downgrading destructive oculocentric, patriarchal ideologies deadening females’ spirit and capability of choice. Coinciding with Louis Althusser’s quest of the way ideology functions in society, the article attempts to explore the metaphorised representation of females through an Angel/Mad binary as well as to examine the prejudiced Freudian psychosexual interpretation of females created by patriarchal Ideological State Apparatus in the context of the Althusserian concept of interpellation.